Empowerment Cadres of Muslimat Nahdlatul Ulama in Stunting Prevention through Nutrition Education in Bangil Pasuruan - Wiwik Winarningsih; Warda El Maida Rusdi; Muhammad Fifin Kombih; Aufar Zimamuz Zaman Al Hajiri; Rima Isna Rahmawati (Community Development Journal, 2023)
Stunting is one of the nutritional problems faced in the world. The prevalence of stunting in Indonesia is 24.4%, while in Pasuruan Regency it is 22.5%. Most people may not understand the term stunting. The purpose of this community service activity is to increase the knowledge of Muslimat Nahdlatul Ulama (NU) cadres in preventing stunting through nutrition education at Bangil Pasuruan. Method: The target participants for this activity are the Management of the NU Bangil Pasuruan Muslimat Branch. The pre-test and post-test were given as a measure of the participant's level of knowledge after being given education. The provision of this education uses electronic media, namely Power Point regarding inviting toddlers and toddler mothers to come regularly to attend "Posyandu", the benefits of local food and food diversity, accompanying young women to drink iron tablets, assisting prospective brides, assisting pregnant women, and assisting babies to get Exclusive breastfeeding. Results and Discussion: This community service activity was done on Saturday, June 12, 2022, at the Management Building of the NU Muslimat Branch, Bangil, Pasuruan. Attended by 32 participants who were NU Muslimat cadres in Bangil Pasuruan aged 40-65 years. There is an increase of 32.58% in scores from the pre-test to the post-test The statistical analysis results showed a significance value of p <0.05, that there was a significant difference in knowledge among participants in the Pre-Test and Post-Test values. The application of the knowledge gained is a comprehensive effort to prevent stunting and improve the quality of human life in creating a superior generation. Conclusion: Participants experience an increased understanding of stunting prevention through providing education in this community service, with the hope that participants will apply their knowledge to contribute to reducing stunting rates in Bangil Pasuruan.